RESPON AGAMA TERHADAP KRISIS LINGKUNGAN:: Studi Implementasi Paradigma Eco-Theology di Pondok Pesantren An-Nur Yogyakarta - Tata, Nur; Fatmawati, Fatimah; Aflaha, Umi (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
Religion not only governs matters of divinity but also the relationship between humans and the environment. In Islam, religion and the environment are inseparable, as maintaining the environment is akin to upholding the five fundamental objectives of Islam (maqasid al-shari’ah). One of the ways religion plays a role in environmental preservation is through religious institutions, which in this research is represented by Pondok Pesantren An-Nur Yogyakarta. This pesantren is an interesting research subject because in 2023, it was categorized as a “Golden Pesantren,” with one of its programs focusing on environmental issues. The approach used in this study is eco-theology, a concept introduced by Joseph Sittler (1960) that examines the connection between spirituality and ecological responsibility. The two issues explored are the theological foundations behind the development of the eco-theology paradigm at Pondok Pesantren An-Nur Yogyakarta and its implementation. The study has revealed that: First, the hadith narrated by Imam Muslim number 131 in Shahih Muslim serves as the theological foundation used by the leaders of Pondok Pesantren An-Nur Yogyakarta. Second, the implementation of the eco-theology paradigm includes; the establishment of a waste management unit named UPT ASRI, specific waste sorting, ecobrick and biopori processing, and the prohibition of bringing plastic waste into the pesantren.